Anti-inflammatory and Anti-hyperuricemic Effect of Ficus benghalensis Bark Extract in Raw 246.7 Cell Line - Sabi, Essa M; Mujamammi, Ahmed H; Sumaily, Khalid M; Dahman, Lotfi S Bin; Althafar, Ziyad M (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Hyperuricemia and inflammation are associated with the etiology and pathogenesis of several metabolic diseases. Controlling the elevated levels of uric acid and inflammation can be a potential therapeutic option for several metabolic diseases. Aim: The current study examined the anti-inflammatory and anti-hyperuricemic properties of Ficus benghalensis bark extract in vitro using murine macrophage RAW 246.7 cells. Materials and Methods: Hydroalcoholic extracts of Ficus benghalensis bark were obtained. Cytotoxicity and cell viability test of the extracts was evaluated by MTT and Trypan blue exclusion assay. Cells were microscopically observed for the presence of dead cells. To explore the anti-inflammatory and anti-hyperuricemic activity, RAW 246.7 cells were induced with lipopolysaccharide and treated at the concentrations of 20, 40, and 60 μg/ml of Ficus benghalensis bark extract and assessed for xanthine oxidase activity, uric acid levels, reactive oxygen species, lipid peroxidation assay, nitric oxide levels and gene expression studies of a pro-inflammatory and anti-inflammatory cytokine such as TNF-α and IL- 10. Results: A dose-dependent reduction in the xanthine oxidase activity when treated with the bark extract with higher inhibition at 60 μg/ml. Reduction in the amount of uric acid, ROS, nitric oxide, and lipid peroxidation are similar to xanthine oxidase activity with a significant decrease in all treated groups and higher reduction at 60 μg/ ml treatment. Gene expression study showed downregulation of TNF-α and upregulation of IL- 10 in treated groups. Conclusion: Our study demonstrates that Ficus benghalensis bark extract exhibits anti-hyperuricemic and anti-inflammatory effects possibly through xanthine oxidase inhibition. The results provide evidence that Ficus benghalensis bark extract may have the potential to treat hyperuricemia and complications related to hyperuricemia.
Keywords: Anti-hyperuricemic; RAW 246.7 cells; Ficus benghalensis bark extract; Antiinflammatory; TNF-α; IL- 10; Lipopolysaccharide